Survival of human immunodeficiency virus type 1 after rinsing injection syringes with different cleaning solutions. - Abdala, Nadia; Crowe, Michelle; Tolstov, Yanis; Heimer, Robert (Substance use & misuse, 2004)
Bleaching of syringes has been advocated to prevent HIV transmission among injection drug users (IDUs). Several reports indicate that IDUs use household products to disinfect syringes instead of bleach. To test their disinfection efficacy, we performed syringe-rinsing simulations with a range of agents used by IDUs trying to disinfect their syringes. No viable HIV-1 was recovered from syringes rinsed with bleach diluted 1:10. Bleach stored at 37 degrees C and rubbing alcohol performed better than water and the other liquids tested, but less well than bleach 1:10. Rinsing syringes with the other liquids was similar to rinsing with water alone. Increasing the rinsing volume did not always increase the effect of rinsing, but the addition of a second rinse consistently increased rinsing efficacy. Bleaching remains the most effective disinfectant among those tested. It is important that IDUs learn the proper techniques for bleach storage and syringe decontamination. Other household products are not effective disinfectants and should be avoided. Because access to sterile syringes may be restricted by laws, public policy, and police practices, bleach retains its importance in the control of the HIV-1 epidemic among IDUs.
Keywords: Disinfectants; Disinfection; HIV-1; Humans; Substance Abuse, Intravenous; Syringes; United States